Optimal Design of Stray Inductance of Busbar in Two-level IGCT Power Module - LIU Jianping; MA Zhenyu; SUN Baotao; LIU Shaoqi (Kongzhi Yu Xinxi Jishu)
Stray inductance of busbar in converter will have serious influence on the turn-off characteristic of IGCTs, and it may increase voltage stress and turn-off losses of IGCTs, even destroy the device. With the analysis on the generating mechanism of stray inductance, it put forward a new method (micro current element method) to optimize busbar stray inductance, simulated the circuit model of the power module including stray inductances with Matlab to emulate the influence of stray inductances on the turn-off characteristic of the device, calculated the key stray inductances of two types of developed power module with ANSOFT Q3D software, and proved the simulation results with the chopping experiment to emulate the difference between the two modules. Further optimization design on the stray inductance of power module was made with the micro current element method.